Elicitation of Anthraquinones with its Associated Enzymic and Non-Enzymic Antioxidant Responses in Morinda Elliptica Cell Culture - Chong, Tzer Miin (2004)
Morinda elliptica (Rubiaceae) cell suspension culture was used as a model system to understand the effects of elicitation and enzymic and non-enzymic antioxidant responses. The kinetic profiles of anthraquinone (AQ) compounds, hydrogen peroxide (H2O2) level, lipid peroxidation and antioxidant vitamins were determined for cultures grown in maintenance (M), intermediary (G) and production (P) medium strategies, and compared with the profiles from callus and leaf. Screening experiments were carried out to select the most suitable elicitors and effective elicitation factors that could enhance AQs without affecting cell growth in G medium. The selected elicitor was then used to study the effects on enzymic and non-enzymic antioxidant responses. High performance liquid chromatographic (HPLC) method was developed to identify and quantify AQ constituents from the two methods of elicitation – medium strategies and jasmonic acid (JA). P medium strategy produced the highest registered cell growth at 49 g l-1, intracellular AQ content at 42 mg g-1 (dry cell weight) DW and H2O2 level at 9 mol g-1 (fresh weight) FW, compared to other media. The extent of lipid peroxidation at 40.4 nmol g-1 FW and total carotenoids at 13.3 mg g-1 FW for cultures in P medium were comparable to the leaf. Vitamin C content in all culture systems was almost half the leaf content. On the other hand, vitamin E was around 400 to 500 µg g-1 FW in 7-day-old cultures from all medium strategies which was 2-fold to the leaf. In P(21) cultures, nordamnacanthal at 5.6 mg g-1 DW and 1-hydroxy-2-methylanthraquinone at 17.2 mg g-1 DW were detected 4-fold and 12-fold, respectively, higher than the roots. The mechanism to counter reactive oxygen species (ROS) in the whole plant and plant cell cultures is dynamic depending on the availability and level of different types of antioxidants.